Electrochemical Study of Sunset Yellow and its Determination in Soft Drink by Differential Pulse Adsorptive Stripping Voltammetry Using Ag-ErGO/GCE - Giang, Le Thi Huong; Trang, Doan Thi Thu; Giang, Dang Minh Huong; Nhan, Pham Thi Thanh; Mai, Nguyen Thi; Bang, Do Trong; Thuong, Nguyen Thi Kim (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 1DO - 10.25073/2588-1140/vnunst.5517, 2023)
The electrochemical behavior of sunset yellow on the glassy carbon electrode modified with silver and reduced graphene oxide has been investigated by cyclic and differential pulse adsorptive stripping voltammetry. The electrochemical behavior of sunset yellow was reversible and adsorptive on the working electrode. The optimal conditions were obtained as follows: Britton-Robinson (BR) buffer at pH 8.0; adsorption potential 0.4 V; adsorption time 50 s; sweep rate 50 mV/s; linearity range from 10 -7 M to 10 -6 M; the limits of detection and quantitation were 2.5 × 10 -8 M and 8.3 × 10 -8 M, respectively. The procedure was successfully applied to determine sunset yellow in soft drink samples.